2014
DOI: 10.1002/lary.24778
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of respiratory epithelial adenomatoid hamartomas of the olfactory clefts in patients with nasal polyposis

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 25 publications
1
28
2
Order By: Relevance
“…It is very interesting a frequent association between nasal polyposis and bilateral REAH of the olfactory cleft. Nguyen et al [7] found that the development of REAH in patients with nasal polyposis is induced by a long-lasting and/or severe inflammation of the nasal mucosa in the olfactory cleft region. A subtype of REAH, chondro-osseous respiratory epithelial adenomatoid hamartoma (COREAH) is an extremely rare entity that contains islands of cartilage and mature bone interspersed throughout the lesion [8].…”
Section: Discussionmentioning
confidence: 99%
“…It is very interesting a frequent association between nasal polyposis and bilateral REAH of the olfactory cleft. Nguyen et al [7] found that the development of REAH in patients with nasal polyposis is induced by a long-lasting and/or severe inflammation of the nasal mucosa in the olfactory cleft region. A subtype of REAH, chondro-osseous respiratory epithelial adenomatoid hamartoma (COREAH) is an extremely rare entity that contains islands of cartilage and mature bone interspersed throughout the lesion [8].…”
Section: Discussionmentioning
confidence: 99%
“…2,4 The term "REAH" is not accurate, as it does not respond to the criteria laid out in the definition of a hamartoma. 2,4 Thus, it is a hyperplasia of the respiratory epithelium rather than a hamartoma. 4 The treatment for REAH is endoscopic surgery without need of a large resection.…”
Section: Discussionmentioning
confidence: 99%
“…2,4 Thus, it is a hyperplasia of the respiratory epithelium rather than a hamartoma. 4 The treatment for REAH is endoscopic surgery without need of a large resection. 2 On the contrary, imaging criteria for the diagnosis of REAH-OCs were the bilaterality of masses in the OC, large OC/small OC ratio <2, and no bone erosion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations